Copper removal using acid activated peanut husk from aqueous solution - Ingle, Pradnya K.; Karishma, Attarkar; Rathod, Virendra K. (Journal of Environmental Engineering and Landscape Management, 2016)
Peanut husk, an agricultural waste is a precursor biomass veteran for chemical activation using phosphoric acid. The work deals with activation of peanut husk using phosphoric acid followed by its application. The effect of various parameters such as impregnation ratio, temperature, particle size and agitation speed on copper adsorption were also studied. Physical characterization of the activated adsorbent was done using SEM, BET and FTIR to understand the modifications. The optimum parameter values of chemical activation influencing adsorption were 20% phosphoric acid concentration, 1:8 acid impregnation ratio, 60 °C activation temperature and 350 rpm stirring speed. The copper uptake was 14.3 mg/g for peanut husk whereas by chemical activation it was increased to 17.88 mg/g. Thus adsorption capacity of peanut husk can be successfully improved using phosphoric acid activation.